Stability and microstructure of powdered pulp of the Palmer mango obtained by the process of lyophilisation - Costa, Laiana; Lara Junior, Jovan; Costa, José Maria; Afonso, Marcos; Rodrigues, Sueli; Wurlitzer, Nédio (Revista Ciência Agronômica, 2019)
The aim of this work was to study the stability of powdered mango pulp obtained through the process of lyophilisation, as well as its structural characteristics using electron microscopy analysis. In response to an earlier experimental design using maltodextrin concentrations of 0%, 10%, 20% and 30% and periods of 24 and 30 hours, the condition of 20% maltodextrin and 24 hours drying was chosen as the best for drying mango in a freeze dryer. The stability study was therefore carried out using powdered mango pulp obtained under the above best-drying conditions, stored for 90 days and monitored every two weeks by analysis of the moisture, ascorbic acid content, b* colorimetric parameter and hygroscopicity. Storage was at room temperature (27 °C) in vacuum and non-vacuum laminated packaging, and in non-vacuum plastic packaging. The vacuum laminated packaging maintained the initial characteristics of the stored product for longer, especially the ascorbic acid content, hygroscopicity and b* colour parameter. The microstructure of the sample was then studied under different concentrations of maltodextrin (0%, 10%, 20% and 30%) so as to understand the effect of the drying agent on the final product. Close-up images of the powder revealed the porous surface formation and the effect of the agent on particle size, where higher concentrations of maltodextrin resulted in more porous powders with smaller particles.